What Can We Learn From a Human-Rights Based Approach to Disability for Public and Patient Involvement in Research? - Browne, Jacqui; Dorris, Emma R. (Frontiers in Rehabilitation Sciences, 2022)
Public and Patient Involvement can align both the research process and its outcomes with the values, needs and expectations of society. By fostering the design of inclusive, engaged, and sustainable practices, research and research integrity can be improved. Devolving power to involve patients and relevant publics in deliberative decision making can produce better research outcomes. People living with disabilities are often categorized as “Hard to Reach”. There is a varied and complex ecosystem of societal challenges of living with a disability that reinforce this. However, if researchers are to meet their obligations under the UN Convention on the Rights of Persons with Disabilities, disabled people should be included in public and patient involvement for all research in which they have a stake. In this article we argue that a better understanding of rights-based approaches and the social model of disability within the wider research community can help to remove barriers to research involvement for disabled persons. Rights based approaches focus on the core principles of participation, accountability, and non-discrimination. We will discuss how these principles can be applied to research involvement, and how their adoption can facilitate truly meaningful PPI in disability research.